PENGGUNAAN MEDIA VIDEO YOUTUBE "SD63 BAGAIMANA MENYIMAK YANG EFEKTIF” DALAM PEMBELAJARAN KETERAMPILAN MENYIMAK - Lasmana Fajar Hapriyanto; Shofia Permata Sari; Mintowati (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2024)
This research discussed the relationship between psycholinguistics and learning listening skills in an educational context. Psycholinguistics is a field of study that combines linguistics and psychology to understand how language is understood, produced and acquired by humans. Learning listening skills, as part of the language acquisition process, displays a close relationship with psycholinguistic concepts. This research used a qualitative method with a descriptive approach to describe the listening process in classroom learning based on video shows available on YouTube "SD63 BAGAIMANA MENYIMAK YANG EFEKTIF". Analysis was carried out on teacher teaching techniques and student responses to listening activities. The research results showed that effective teaching methods require the application of psycholinguistic principles, such as the use of clear intonation and appropriate speed in delivering material. The aims of this research were (1) to find out how listening skills relate to psycholinguistics, (2) to find out good listening learning models to be implemented in the future, (3) to analyze listening learning videos, both inappropriate learning and inappropriate listening learning. it's right. This research provided a deeper understanding of the importance of integrating psycholinguistic concepts in learning listening skills to increase the effectiveness of the learning process.